UPAYA MANAJEMEN KEPOLISIAN DALAM PENANGANAN TINDAK PIDANA KEJAHATAN DENGAN MODUS PERAMPASAN SECARA PAKSA - Made Ayudina Sancitami Prakasa; Taufik Rachman (Universitas Mataram, 2022)
People who lack skills, low education and economic conditions have a tendency to get money in any way, one of which is committing the crime of theft. Surabaya is one of the cities whose community activities never stop so that it can trigger acts of theft by criminals. The rise of incidents of theft with violence at this time has become a concern for the police to maintain order and public comfort. Theft accompanied by violence is regulated in Article 365 paragraph (1) of the Criminal Code. The purpose of this study is to provide an overview of violent theft and invite the public to actively participate in preventing and eradicating all modes of theft. The results are expected to be useful for making appropriate policies in suppressing violent theft. This research consists of 2 stages, the first stage is a descriptive study with a qualitative method by analyzing primary data from the Surabaya Police Criminal Investigation Unit. The second stage is the formulation of a solution as a police management effort in handling criminal acts of crime with the mode of forcible confiscation. The result is that this modus operandi of confiscation has become a